Equivalent J-inverter network parameters analysis and cancellation of spurious response of parallel coupled microstrip line - Marimuthu, Jayaseelan; Esa, Mazlina (IEEE, 2006)
In this paper, the frequency-dispersive characteristic of a two-port parallel coupled microstrip line (PCML) is presented using equivalent J-inverter network parameters which were obtain from its admittance parameters. The extracted J-inverter parameters, J-susceptance and electrical line length, were used to obtain the transmission zero frequency, fundamental response frequency and harmonic response frequency of the PCML. The transmission zero frequency can be realigned by varying a centrally located single groove size to suppress the first spurious harmonic passband of the filter. A technique was identified by using J-inverter parameters to cancel the spurious response. It was found that the transmission zero of J-susceptance null of the PCML can be realigned to cancel the first harmonic resonance. This was done by using a single groove with specific dimension. The proposed technique was justified by two single-stage bandpass filter of PCML with tight coupling characteristic.